Innovative security solutions for information technology and communications : 11th International Conference, SecITC 2018, Bucharest, Romania, November 8-9, 2018, Revised selected papers /: 11th International Conference, SecITC 2018, Bucharest, Romania, November 8-9, 2018, Revised selected papers. (2019) - Unknown
No abstract available